Efficacy of two mouthwashes with cetylpyridinium chloride: a controlled randomized clinical trial - Cassiano Kuchenbecker RÖSING; Juliano CAVAGNI; Eduardo José GAIO; Francisco Wilker Mustafa Gomes MUNIZ; Nicolle RANZAN; Harry Juan Rivera OBALLE; Stephanie Anagnostopoulos FRIEDRICH; Raísa Maldonado SEVERO; Bernal STEWART; Yun Po ZHANG (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract This study aimed to evaluate the anti-plaque and anti-gingivitis effects of two mouthwashes containing cetylpyridinium chloride (CPC), in comparison to negative control mouthwash. One hundred and twenty subjects were randomly assigned to study groups: test (0.075% CPC and 0.28% zinc lactate), positive control (0.07% CPC) and negative control mouthwash without CPC. All volunteers were examined by a calibrated examiner for the Quigley-Hein Plaque Index (Turesky modification) and Löe-Silness Gingival Index (GI). Gingival severity was also measured by the percentage of sites with positive gingival bleeding. During six weeks, oral hygiene consisted of brushing twice daily with a toothbrush and toothpaste and rising with their assigned mouthwash. Plaque and gingival parameters were assessed at baseline, after four and six weeks of product use. Statistical analyses were performed separately for plaque and gingival indices, by ANOVA, paired t-test and ANCOVA (α < 0.05). After 4 and 6 weeks, all mouthwashes groups presented statistically significant reductions in plaque and gingival parameters as compared to baseline. In comparison to the positive control, the test group presented additional reductions in dental plaque of 19.8% and 16.8%, after 4 and 6 weeks, respectively. For GI, the additional reductions in the test group were 9.7% and 14.3%, at 4 and 6 weeks, respectively. The test group showed additional reduction of 35.3% and 54.5% in the gingival severity, at week 4 and 6, respectively. It is concluded that the mouthwash containing CPC and zinc lactate presents significant anti-plaque and anti-gingivitis effects as compared to positive and negative control mouthwashes.